The effects of entrepreneurial orientation and business model innovation towards company performance by observing the factor of formalization and the information technology capability - Eko Prasetyo (President University, 2021)
This research investigates the effects of entrepreneurial orientation in the innovation of business models that affects the increase of company performance in the application and games industry. The formalization that is present in the organizational structure and capabilities of information technology can affect the orientation of entrepreneurial orientation. The research data is accumulated from 64 companies, through the implementation of the purposive sampling method. The data analysis is done by using the Structural Equation modelling (SEM) with the method of Partial Least Square (PLS). The result of the study shows that the level of formalization does not have any impact on the orientation of entrepreneurial orientation. Information technology capability is vital to the development of the entrepreneurial orientation. To increase its performance, companies of applications and games must continuously develop its business model innovation. Further research is expected to be able to develop the idea for other creative industries and add other variables that influence the entrepreneurial orientation as well as the business model innovation.